(untitled) (Itinera, 2024)
In biology, mimesis includes imitation between individuals of the same species – the study object of behavioral sciences and neurophysiology – and mimicry between different species through traits or behaviours generally common to all individuals – to be analyzed from an evolutionary and morphogenetic perspective. Mimicry is widespread among representatives of many animal lineages, but has been also recorded among plants. Mimicry is very often adaptive, e.g. because of protection produced by the similarity of a harmless animal to a poisonous or otherwise dangerous one (Batesian mimicry, e.g., false vs. true coral snakes, or hoverflies vs. wasps), or by sharing of closely similar livery by animals protected by different weapons (Müllerian mimicry). Less conventional kinds of mimicry include the aggressive behaviour of some fireflies imitating the flashing of a different species on which they prey; the intraspecific Müllerian mimicry between larva and adult of some ladybirds; and the presence of identical compounds in the sexual pheromone produced by a female wasp and in the fragrance of the orchid species pollinated by the male. Morphological and biochemical similarity cannot be explained by selective advantage only. Even in cases of adaptive mimicry, shared developmental constraint may facilitate the evolution of similarity between model and mime.